The Chinese city - Wu, Weiping 1965-; Gaubatz, Piper Rae Professorin für Stadtgeographie 1962- (Routledge, Taylor & Francis Group, 2021)
"Drawing on years of research experience and keen observations of the triumphs and problems in China's cities, the authors provide a foundational understanding of China's urbanization and cities that is grounded in history and geography and challenges readers to consider Chinese urbanization through multiple disciplinary and thematic lenses. Intended for a wide audience in higher education and beyond, this book will be useful to readers interested in Chinese Studies, East Asian Studies, Urban Studies, Urban Geography, or Urban Planning"--